Chirbes’ "En la orilla" and the image of father after Kafka - Rivas Hernández, Ascensión (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
On the Edge, by Rafael Chirbes, has been acknowledged as the great novel about the Spanish 2008 economic crisis. In this paper, nevertheless, the novel is analysed from an original perspective, that of the relationship between a father and his son, since the story is built upon the bond that ties Esteban and his father. In order to do so, the novel is compared to Kafka´s heartrending Letter to His Father. From this new point of view, Chirbes’ novel reaches a universal value. In addition, it´s important to study the narrative point of view, that moves from homodiegetical to heterodiegetical in order to make the father´s story trustworthy.